Delayed speech development in children: Introduction to terminology - M. Yu. Bobylova; T. E. Braudo; M. V. Kazakova; I. V. Vinyarskaya (Русский журнал детской неврологии, 2017)
There has been recently an increase in the number of children diagnosed with delayed speech development. There is delay compensation with age, but mild deficiency often remains for life. Delayed speech development is more common in boys than in girls. Its etiology is unknown in most cases, so a child should be followed up to make an accurate diagnosis. Genetic predisposition or environmental factors frequently influence speech development. The course of its delays is various. In the history of a number of disorders (childhood disintegrative disorder, Landau–Kleffner syndrome), there is evidence for the normal development of speech to a certain period and then stops or even regresses. By way of comparison, there are generally speech developmental changes in autism even during the preverbal stage (a complex of revival fails to form; babbling is poor, low emotional, gibberish; at the same time, the baby recipes whole phrases without using them to communicate). These speech disorders are considered not only as a delay, but also as a developmental abnormality. Speech disorders in children should be diagnosed as early as possible in order to initiative corrective measures in time. In this case, a physician makes a diagnosis and a special education teacher does corrective work. The successful collaboration and mutual understanding of the specialists in these areas will determine quality of life for a child in the future. This paper focusses on the terminology and classification of delays, which are necessary for physicians and teachers to speak the same language.